Young fecal transplantation mitigates the toxicity of perfluorobutanesulfonate and potently refreshes the reproductive endocrine system in aged recipients - Chenyan Hu; Mengyuan Liu; Baili Sun; Lizhu Tang; Xiangzhen Zhou; Lianguo Chen (Environment International, 2022)
The aging process leads to the gradual impairment of physiological functions in the elderly, making them more susceptible to the toxicity of environmental pollutants. In this study, aged zebrafish were first transplanted with the feces from young donors and subsequently exposed to perfluorobutanesulfonate (PFBS), an emerging persistent toxic pollutant. The interaction between young fecal transplant and PFBS inherent toxicity was investigated, focusing on reproductive performance and the underlying endocrine mechanism. The results showed that PFBS single exposure increased the percentage of primary oocytes in aged ovaries, implying a blockage of oogenesis. However, transplantation of young feces completely abolished the effects of PFBS and promoted oocyte growth, as inferred by the obviously lower percentage of primary oocytes, accompanied by a higher percentage of cortical-alveolar oocytes. Measurement of sex hormones found that PFBS significantly increased the blood concentration of estradiol and disrupted the balance of sex hormones in the elderly, which were, however, efficiently ameliorated by young fecal transplantation. Based on gene transcription along the hypothalamic-pituitary–gonadal axis, hierarchical clustering analysis showed similar profiles of the reproductive endocrine system between young zebrafish and their aged counterparts transplanted with young feces, implying that young fecal transplantation might refresh the endocrine system of aged recipients, regardless of PFBS exposure. The increased transcription levels of mRNAs encoding vitellogenin, activinBA, and membrane bound progestin receptors would cooperatively enhance the growth and maturation of oocytes in the ovaries of aged zebrafish receiving young fecal transplantation. Overall, the findings highlighted the potent efficacy of young fecal transplantation to improve the reproductive function of the elderly and to mitigate the endocrine disruption of an environmental pollutant. These findings are expected to broaden our understanding of the efficacy, mechanisms, and application of fecal transplantation.